2015
DOI: 10.1111/aos.12672
|View full text |Cite
|
Sign up to set email alerts
|

Corneal biomechanical characteristics measured by the CorVis Scheimpflug technology in eyes with primary open‐angle glaucoma and normal eyes

Abstract: ABSTRACT.Purpose: To evaluate the biomechanical properties of the cornea using Corneal Visualization Scheimpflug Technology (CorVis ST, Oculus) in eyes with primary open-angle glaucoma (POAG) and normal control eyes. Methods: A comparative cross-sectional study that included 42 patients with POAG and 60 normal control subjects matched for intraocular pressure (IOP) and central corneal thickness (CCT). IOP was measured with a Goldmann applanation tonometer (GAT). Corneal tomography and biomechanical parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
1
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 24 publications
7
54
1
9
Order By: Relevance
“…Previous studies have considered DA as an exclusively corneal phenomenon [10][11][12] ; however, this study provides evidence of the distribution and significant difference between DA (provided by the device) and the isolated corneal (MCD) and orbital (MOD) components in a population of healthy corneas. Isolation of the orbital component should be used when analyzing deformation characteristics in diseases that only affect the cornea.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous studies have considered DA as an exclusively corneal phenomenon [10][11][12] ; however, this study provides evidence of the distribution and significant difference between DA (provided by the device) and the isolated corneal (MCD) and orbital (MOD) components in a population of healthy corneas. Isolation of the orbital component should be used when analyzing deformation characteristics in diseases that only affect the cornea.…”
Section: Discussionmentioning
confidence: 68%
“…This is in agreement with Leung et al, 11 who demonstrated a statistically significant, weak relationship (r ¼ 0.002) between age and DA in a group of normal, glaucoma, and glaucoma-suspect eyes. Tian et al 12 also described a significant positive correlation (r ¼ 0.43) between age and DA. Conversely, others have discovered no significant correlations between age and DA.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…16 Several articles have recently been published on the possible applications of the Corvis ST, particularly evaluating possible biomechanical differences in the cornea after undergoing refractive surgery procedures, [17][18][19][20][21][22] between normal and keratoconic patients, [23][24][25][26] after cross-linking, 27 and in patients with glaucoma. [28][29][30][31] However, it has been demonstrated that IOP and pachymetry have important influences on most corneal biomechanical metrics provided by both the Corvis ST and ORA. [32][33][34] It is therefore relevant to investigate the distribution and normal limits for the in vivo corneal biomechanical data derived from dynamic corneal response parameters, and determine whether these metrics have correlations with IOP and corneal thickness.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7]10,[14][15][16][17][18][19][20]29,32,33 Other studies have found that other baseline factors such as axial length, 21,23 age, 27 and CCT 23 also are significantly associated with corneal biomechanical parameters. To accurately understand the relationship between corneal biomechanics and ocular diseases, the effect of baseline factors on corneal deformation parameters must be clarified.…”
Section: Discussionmentioning
confidence: 99%